Antenatal nephromegaly and propionic acidemia: a case report - Ségolène Bernheim; Georges Deschênes; Manuel Schiff; Isabelle Cussenot; Olivier Niel (BMC Nephrology, 2017)
Abstract Background Propionic acidemia (PA) is a rare but severe recessive autosomal disease, presenting with non specific signs in the first years of life. Prenatal diagnosis is invasive (amniocentesis) and limited to suspect cases. No screening test has been described, in particular no correlations between prenatal sonography and PA have been documented so far. Case presentation We report the case of a boy with fetal bilateral nephromegaly and hyperechogenic kidneys, along with neonatal acute kidney injury; no etiology could be found in the first months of life. At 3 months of life, he presented with tachypnea and altered mental status, which lead to the diagnosis of PA. The renal ultrasound at 8 months of life, after a symptomatic treatment of PA had been initiated, showed a regression of the renal abnormalities. Conclusion This case describes PA as a novel cause of large and hyperechogenic kidneys in the antenatal period. It suggests that, when confronted to fetal nephromegaly, hyperechogenic kidneys and risk factors of metabolic disease such as consanguineous parents, PA should be considered, and a prenatal test should be proposed.